2016
DOI: 10.1109/tip.2016.2518082
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Color Difference: Residual Interpolation for Color Image Demosaicking

Abstract: In this paper, we propose residual interpolation (RI) as an alternative to color difference interpolation, which is a widely accepted technique for color image demosaicking. Our proposed RI performs the interpolation in a residual domain, where the residuals are differences between observed and tentatively estimated pixel values. Our hypothesis for the RI is that if image interpolation is performed in a domain with a smaller Laplacian energy, its accuracy is improved. Based on the hypothesis, we estimate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 32 publications
0
104
0
Order By: Relevance
“…Kiku and Y. Monno et al [34] showed that accuracy of interpolation has improved via reducing the image Laplacian energy. From the observation, the proposed MLRI performs an interpolation under a residual domain, with minimal Laplacian Energy (LE).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiku and Y. Monno et al [34] showed that accuracy of interpolation has improved via reducing the image Laplacian energy. From the observation, the proposed MLRI performs an interpolation under a residual domain, with minimal Laplacian Energy (LE).…”
Section: Related Workmentioning
confidence: 99%
“…From the observation, the proposed MLRI performs an interpolation under a residual domain, with minimal Laplacian Energy (LE). For better optimization, D. Kiku [34] also proposed an algorithm that is Novel demosaicing algorithm. Through incorporating the MLRI approach [35] into GBTF algorithm [36], is one of a modern Bayer demosaicing algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…The residual interpolation (RI) method has been widely used recently [19][20][21][22][23][24][25]. The RI algorithm exploited the characteristics of the guided filter [26] and showed outstanding performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…This method has proven to be effective. Due to the prominent impact of a precise tentative estimate on the performance of the algorithm, KiKu et al proposed minimized-Laplacian residual interpolation (MLRI) [12] to tentatively generate a more accurate estimate and introduced a weighted average in the guide filter [13]. Valuable information can be obtained from these two articles.…”
Section: Introductionmentioning
confidence: 99%